Relationship between attachment style and depressive symptoms in postpartum women: Findings from Turkey - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2006)
Objective: The present study aimed to investigate the association between depressive symptoms and attachment style in postpartum women in a non-western setting. Method: This study was carried out at the local health care centers in April 2004 among Turkish mothers within 2 to 18 months postpartum. A sociodemographic data sheet and the Turkish versions of Edinburgh Postnatal Depression Scale (EPDS) and Adult Attachment Style Questionnaire (AAQ) were administered to 80 mothers. Results: On the EPDS, 30% of the sample (n=24) displayed symptoms of depression with a cut-off score of >= 11. Postpartum depressive symptoms (EPDS ? 11) were found to be associated with insecure attachment style (X-2=4.42, p=0.035; X-2=10.81, p=0.001 for Part 1 and Part 2 of AAQ, respectively). Conclusion: Maternal insecure attachment behavior, stimulated by the close relationship with the infant may contribute to the factors that may give rise to symptoms of depression. The present study, performed in a non-western country, confirms the results of the previous western studies suggesting a relationship between insecure attachment style and postpartum depression (PPD). Clinicians should pay particular attention to vulnerable women regarding their attachment style for early identification and treatment of PPD, either in western or non-western societies.
Keywords: postpartum depression; object attachment; women; cross-cultural comparison; POSTNATAL DEPRESSION; ADULT ATTACHMENT; PREVALENCE; PATTERNS; DISORDER; RISK